Emerging themes of the leadership and green innovation of the government-linked companies - Ishak, Noormaizatul Akmar; Ahmad, Hartini (2011)
The main reason businesses need to innovate is due to its necessity to sustain and survive, and not for the matter of how brilliant and visionary the leaders of the organisation are. Innovation has known for its very significant role in the organisation progression and growth. Innovation can happen in the products, processes, and services being embark by organisations to make more profit by reducing operational cost and making processes more efficient. The concern over the environment all around the world has encouraged innovation to be more tailored to the “green”. “Green” is a name that being associated with anything or any action that has impact to the environment such as green building, green government and green innovation. This constructive research is a qualitative multicases study.Data collection is done via interviews, focus group discussions and document analysis. The result has been analyzed and to see the themes emerge from the data before the analysis being interpreted. This paper discusses the impact of green innovation to the top management leadership in the Governmentlinked Companies (GLCs) in Malaysia. The key findings highlighted that the leadership must be sensitive and understand the green demand and situational in the Malaysia and around the world with respect to the industries that these GLCs are operated. This is where the top management leadership “attribute” is justified to fit the green innovation implementation.